Matily herbal drink could be a prophylaxis and therapy against COVID-19: a possibility - Eapen, John T. (International Journal of Research in Medical Sciences, 2021)
COVID-19 (SARS-CoV-2) known as coronavirus is a pandemic and a threat to humans the world over. There are no medicines available to kill the virus; we can control only its spread to some extent. Under such conditions, they have suggested the use of surfactant to kill viruses. We propose the use of a herbal concoction with ingredients available in every kitchen. It has not only emulsification and surfactant properties which inactivate the virus but also subsides Gastroesophageal Reflux Disease (GERD) associated with COVID-19 infection with no proton pump inhibitor. This will favour the inactivation of coronavirus by low pH in the gastric region. Thus, Matily Herbal Drink may act as a prophylaxis and treatment for COVID-19.